Optimization of Soursop (Annona muricata L.) Leaf Extract in Nanoemulgel and Antiacnes Activity Test Against Propionibacterium acnes, Staphylococcus aureus, Staphylococcus epidermidis Bacteria - Asyhari, Hanif Fibiana; Cabral, Kibedi B; Wikantyasning, Erindyah R (Pharmacon: Jurnal Farmasi Indonesia, 2023)
Soursop leaf extract (Annona muricata L.) has antibacterial activity with active components of alkaloids, flavonoids, steroids, and saponins. This research aims to optimize the use of VCO, Tween 80, and PEG 400 in the nanoemulsion system, which will be added Carbopol 940 as a gelling agent to form a nanoemulgel and to determine antibacterial activity. By utilizing the simplex lattice design method in Design Expert 13.0, the nanoemulsion formula has been successfully optimized involving a mixture of VCO, Tween 80, and PEG 400. A total of 14 different nanoemulsion formulas were produced through this process. The process of making nanoemulsion is carried out by mixing extracts, oils, surfactants and cosurfactants, homogenized using a vortex, then sonicated. Evaluation of % transmittance, emulsification time, and pH were carried out to determine nanoemulsion physical properties. The nanoemulsion optimal formula was evaluated for particle size, polydispersity index, and zeta potential and made into nanoemulgel with the addition of Carbopol 940. The optimal formula has a composition of 10.86% VCO, 67.33% Tween 80, 21.81% PEG 400 form homogeneous and clear nanoemulsion with % transmittance of 91.97±1.11%, emulsification time of 56.42±0.72 seconds, and pH of 5.67±0.24. Particle size, polydispersity index, and zeta potential of the optimal formula were 229.47±38.79 nm, 0.41±0.10, and -39.13±0.19 mV, respectively. Evaluation of nanoemulgel physical properties showed homogeneous, pH value of 5.83±0.24, spreadability of 5.57±0.25 cm, adhesive force of 3.80±0.25 seconds, viscosity of 11479.33±167.49 cP, antibacterial activity against P. acnes, Staphylococcus aureus, and Staphylococcus epidermidis with inhibition zone diameters of 9.67±0.47 mm, 7.33±0.47 mm, and 5.67±0.47 mm. respectively. Nanoemulgel soursop leaf extract has suitable physical properties, and antibacterial activity is in the medium category.